STRATEGIC COMMUNICATION IMPACT IN SHAPING ECONOMIC POLICIES AND MOBILISING RESOURCES FOR DEVELOPMENT - Elvis Madondo; Hummerly Dhobha; Thandeka Ngcobo (Baltic Journal of Economic Studies, 2025)
Developing economies, which were the most ambitious in the 21st century, have struggled to mobilise enough financial resources, leading to modest progress in achieving the Sustainable Development Goals. This study examines the role of strategic communication in shaping economic policies and mobilising resources for development in emerging economies, with a focus on South Africa, Brazil, and Indonesia. The research adopts a qualitative approach, using case studies to explore how governments in these countries utilise strategic communication to influence public opinion, inspire investor confidence, and promote sustainable economic growth. The findings indicate that effective strategic communication in developing nations can significantly enhance public support for economic reforms and policies, improve transparency, and foster stakeholder engagement. The application of framing theory and stakeholder theory provides valuable insights into how governments can craft messages that resonate with both domestic and international audiences, thus promoting economic resilience. Key factors such as risk communication, stakeholder involvement, and transparency are identified as crucial to the success of economic policies. This study highlights that strategic communication goes beyond mere information dissemination; it involves aligning policies with the values and priorities of key stakeholders. Additionally, the integration of digital platforms is emphasised as an essential tool for broadening outreach and countering misinformation. While the study offers valuable recommendations for policymakers, such as enhancing framing strategies and leveraging digital communication, it also acknowledges several limitations, including its geographical focus and reliance on secondary data. The research concludes by suggesting future research avenues, including comparative studies across different regions and longitudinal studies to assess the long-term impact of strategic communication on economic development.